Experimental investigation on the hydrodynamic performance of a pile-supported OWC-type breakwater (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The present study considers the design optimisation of an Oscillating Water Column (OWC) incorporated into a pile-supported breakwater structure. This has been achieved by performing a substantial number of scaled physical model tests and a methodical variation of key device parameters within multiple configurations. The key aspects that have been investigated include: (a) the geometric characteristics of the breakwater structure, (b) the pneumatic efficiency of the OWC, (c) the geometry of the OWC chamber and (d) the relative position of the OWC chamber within the breakwater. The present work considers (monochromatic) regular waves of varying steepness and effective water depth as incident wave conditions. The efficiency of the designed structure in terms of shore protection capacity and wave energy extraction was assessed by quantifying relevant transmission coefficients and the power output metrics. This has been achieved by using a combination of collocated and complementary measuring devices, such as arrays of wave gauges, pressure transducers and a high-definition video camera. The study concluded that systematic refinement of the geometrical parameters can substantially enhance the overall hydrodynamic efficiency of a pile-supported OWC breakwater. Additionally, it was found that a configuration featuring a chamber positioned in front of the breakwater, with a relative chamber breadth of 0.67, outperforms wider breadth configurations in terms of both energy extraction efficiency and reduction of the transmission coefficient. Taken together, the present study provides an in-depth analysis of the effects of key design parameters of a breakwater-integrated OWC, its efficiency and shore protection potential.